The “Methyl-CpG Binding Domain Protein 2” Plays a Repressive Role in Relation to the Promoter CpG Content in the Normal Human Cell Line MRC5 - Perriaud, Laury; Lachuer, Joel; Dante, Robert (Current Pharmaceutical Design, 2014)
In cancer cells, methylation-dependent gene silencing is at least partly mediated by the “Methyl-CpG-Binding Domain protein 2” (MBD2 protein), via the recruitment of chromatin remodeling complexes. However this repressive role was poorly investigated in normal cells. To identify the genes repressed by MBD2 in these cells, we have determined the impact of MBD2 depletion on gene expression in human embryonic MRC5 fibroblasts, using RNA inference combined with microarray analysis. The up-regulation of some randomly selected genes was confirmed and a direct association between gene repression and MBD2 binding on methylated promoters associated to these genes was subsequently established. This control of gene expression appears to depend on the CpG content of promoters as MBD2 depletion was not sufficient to induce the expression of silent genes associated with High-CpG promoters, but it was required to achieve the methyl-dependent transcriptional locking of the genes associated with promoters exhibiting intermediate CpG content. Therefore, MBD2 seems to play a selective role in gene repression depending on the CpG content of the promoter regions.
Keywords: methyl-DNA binding protein